The Relationship between Bullying, Organizational Silence and Sports Behaviors of Secondary School Students - Tan, Çetin; Namlı, Aysel Kızılkaya; Yagmurlu, Nese (My University, 2024)
This research was conducted to examine the perceptions of bullying, organizational silence and sports of secondary school students. According to the results of the research, the vast majority of the participants (75%) stated that they broke the rules at school. First of all, almost half of the participants stated that they prefer not to be exposed to bullying. Participants stated that they tried to explain the situation in general to those they thought were superior. In addition, resorting to physical violence, using psychological superiority and being patient are among the opinions expressed. It was determined that there were the same behaviors in the reactions given to them or given by themselves in the face of these behaviors. In the study, when the participants showed a bullying attitude to their friends, they stated that they would generally intervene and apply solutions in different ways in their own way.
Keywords: Secondary school students; sports; organizational silence; Bullying